PENILAIAN HASIL PENYULUHAN CARA AMAN DAN NYAMAN BEROBAT GIGI SELAMA PANDEMI COVID-19 PADA KOMUNITAS HIMPUNAN MAHASISWA SASTRA INDONESIA, UNIVERSITAS NASIONAL, JAKARTA SELATAN - Aditya P. Sarwono; Carolina D. Marpaung; Rosalina Tjandrawinata; Armelia S. Widyarman (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic, which has been running for almost two years, is one of the factors that hinder patients from going to the doctor especially to the dentist. However, delaying dental treatment is a dilemma given that teeth are an important organ and affect a person's quality of life. Delaying dental treatment causes more severe complaints or disturbances, forcing them to keep coming to the dentist. The condition of having to open a mask and mouth in dental care creates anxiety and discomfort in patients during a pandemic. There are still many people who do not know how to safely and comfortably dental treatment during a pandemic, especially among students. This is the main reason for conducting counseling on safe and comfortable tips to dentists in the COVID-19 era, such as the use of Teledentistry, health protocols, and anxiety management during dental treatment, in the context of implementing Community Health Service by the Faculty of Dentistry, Trisakti University in accordance with the vision the mission of the Tridharma in the field of Community Service. The results of the questionnaires provided showed an increase in knowledge about safe and comfortable ways of getting dental treatment during the Covid-19 pandemic. Keywords : Teledentistry, Health Protocol, Anxiety Management, Dental Treatment, Covid-19 Pandemic